Advances in immunology - Alt, Frederick W. (Advances in immunology, 2020)
Advances in Immunology, Volume 146, the latest release in a long-established and highly respected publication, presents current developments and comprehensive reviews in immunology. Articles address the wide range of topics that comprise immunology, with this release focusing on The design of vaccine strategies to elicit HIV-1 broadly neutralizing antibodies, T cells in latent viral infections, Preserving Immune Homeostasis with A20, Transcriptional control in the context of innate and adaptive lymphoid development, RAG and AID structural biology and the important insights it has generated for the V(D)J recombination and CSR/SHM fields, and more.